PEMBERIAN KACANG KORO PEDANG (CANAVALIA ENSIFORMIS L) HASIL FERMENTASI DENGAN RAGI TEMPE (RHYZOPUS OLIGOSPORUS) TERHADAP PERFORMA PRODUKSI AYAM KAMPUNG - Sri Utami (Bajang Institute, 2022)
The air of this study was conducted to evaluate response of broiler to diet that containing fermented jack bean by Rhyzopus olisgosporus based on feed intake, weight gain,feed conversion. The experiment was designed in Completely Randomized Design with 4 treatments and 4 replications. The treatments are R0:control feed without fermented jack bean, R1:92,5% R0 + 7,5% fermented jack bean, R2: 85% R0 + 15% fermented jack bean, R3: 77,5% R0 + 22,5% fermented jack bean. Data were analyzed using variance analysis followed by Duncan Multiple Range Test. The result shows that free-range chicken gave similar response to feed containing fermented jack bean. Conclusion that can be drawn is fermented jack bean seed fermented by Rhyzopusoligosporus can be applied in the free-range chicken diet up to 22,5%.